Prawa człowieka: czasowo wyłączone z użytku. Narracja i praktyka w czasach pandemii - Zsögön, Cecilia (Pedagogika Społeczna Nova, 2021)
What is the origin of the narrative of human rights? What interests do they represent? Can human rights help reverse the devastating consequences of the COVID-19 pandemic on impoverished children? To an- swer this question, we will discuss the origin of the narrative and discourse of human rights and their po- tential as enforcement mechanisms for reversing vulnerability, preventing abuses and promoting solidarity and justice. Despite their promise, the past decade has seen a backlash against human rights on almost every front, worsened by the coronavirus outbreak which is causing a widespread global disruption and exacerbating pre-existing inequalities. We consider the impact on vulnerable children in Latin America, which has greatly worsened since the spread of coronavirus. Finally, we discuss the impact of pandemic on children ́s rights, as well as initiatives relating to increasing their level of protection and guaranteeing to the exercise of their rights, which have been severely compromised during these turbulent times.